Comparative study of the different surface conditions on the bending properties and topographic analysis of the fiberglass posts - Ortega Condori, Myriam Rosmery (2022)
Objectives: To evaluate the bending and topography properties of surface treated fiber posts. Material and Methods: Experimental, In vitro. The samples were divided into two groups, the flexibility of 40 fiberglass posts from 2 commercial houses was evaluated for each conditioning procedure P1: FGM White Post DC; P2: MAQUIRA Fiber Post. The conditioning techniques were: T1: control T2: Hydrofluoric Acid 10% 15 seconds T3: Hydrogen Peroxide 24% 60 seconds T4: aluminum oxide 50 µm and were subjected to the universal testing machine, for the bending test of 3 points. The topographic surface of the fiberglass posts was observed using a scanning electron microscope. Results: The deflection (mm) showed a significant difference comparing the control groups and the conditioned groups with an average maximum value of 0.59mm ±0.04 and a minimum value of 0.51mm ±0.06. In the maximum force (N), a significant difference was observed when comparing the control groups and the conditioned groups, with a maximum value of 133.68 ±11.42 N and a minimum value of 103.48 ±17.79 N. Conclusions: No adverse effects on bending properties were found for both groups of fiberglass posts after surface conditioning with the different protocols.